Molecular prevalence and genotypic distribution of human pegivirus-1 among Iranian hemodialysis patients - Amin Naseri; Enayat Anvari; SeyyedehMasumeh Mirnurollahi; Abolfazl Fateh (Virus Research)
This study investigates the molecular prevalence and genotypic distribution of Human Pegivirus-1 (HPgV-1) in Iranian hemodialysis (HD) patients. A case-control study was conducted from May 2017 to December 2024, including 1576 HD patients and 1000 age- and gender-matched healthy individuals. Serum samples were analyzed using nested PCR and sequencing of the 5′-UTR region to detect HPgV-1 RNA and determine genotypes. The prevalence of HPgV-1 was significantly higher in HD patients (13.6 %) compared to healthy controls (0.6 %). Among HPgV-1-positive HD patients, only genotype 2a was identified. Co-infections were notable, with 11.8 % of HPgV-1-positive patients also infected with HCV (predominantly genotype 3a), 3.0 % with HBV, and 11.7 % with HIV. Interestingly, HCV co-infected patients exhibited lower liver enzyme levels, while those co-infected with HIV had significantly higher CD4+ T cell counts (605.2 ± 198.7 vs. 412.3 ± 156.8 cells/mm³, P < 0.001), suggesting potential immunomodulatory effects of HPgV-1. Additionally, factors such as prolonged dialysis duration, elevated urea levels, and older age were significantly associated with HPgV-1 positivity. These findings underscore HD as a major risk factor for HPgV-1 transmission, likely exacerbated by hospital-acquired practices in dialysis units. The observed associations between HPgV-1 and improved clinical parameters in co-infected individuals highlight its complex role in viral pathogenesis, warranting further investigation into its underlying mechanisms. This study emphasizes the urgent need for stringent infection control measures in dialysis settings to mitigate viral transmission.